The Moderating Role of Market Ratio on the Effect of Profitability and Liquidity toward Corporate Sustainability Disclosure - Muhammad Iif Fahruddin; Bustanul Ulum; Anisaul Hasanah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study examines the effect of profitability and liquidity on Sustainability disclosure and investigates the moderating role of market ratio in manufacturing companies listed on the Indonesia Stock Exchange during the 2024–2026 period. Increasing global attention to Environmental, Social, and Governance (ESG) issues has encouraged companies to improve transparency through Sustainability disclosure; however, the level of disclosure varies across companies. This research employs a quantitative explanatory approach using secondary data obtained from annual financial reports, Sustainability/ESG reports, and stock price data. The sample consists of 50 manufacturing companies selected through purposive sampling techniques. Data analysis was conducted using multiple linear regression analysis with the assistance of SPSS version 26. The results indicate that profitability and liquidity have a positive and significant effect on Sustainability disclosure. Furthermore, market ratio is proven to moderate the relationship between profitability and liquidity toward Sustainability disclosure by strengthening these relationships. The findings suggest that companies with stronger financial performance and favorable market valuation tend to disclose Sustainability information more comprehensively. This study contributes to the development of Sustainability reporting literature and provides practical implications for companies and investors in assessing corporate Sustainability performance.